2018
DOI: 10.1097/nmd.0000000000000905
|View full text |Cite
|
Sign up to set email alerts
|

Change in Emotional and Theory of Mind Processing in Borderline Personality Disorder

Abstract: Changes in emotion processing (EP) and in theory of mind (TOM) are central across treatment approaches for patients with borderline personality disorder (BPD). Whilst the assessment of EP relies on the observation patient's self-criticism in a two-chair dialogue, individual's TOM assessments is made based on responses to humorous stimuli based on false beliefs. For this pilot study, we assessed eight patients with BPD before and after a three-month long psychiatric treatment, using functional magnetic resonanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

6
2

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 60 publications
0
18
0
Order By: Relevance
“…We demonstrated the feasibility of the pre-post design [109]. We demonstrated in medication-free, righthanded female patients with BPD (N = 8), who were undergoing a 10-session psychiatric treatment, that hypotheses 1 and 2 may be confirmed (due to the small sample size, the analyses for hypotheses 3 and 4 were not tested).…”
Section: Feasibility: Results From the Pilot Studymentioning
confidence: 93%
“…We demonstrated the feasibility of the pre-post design [109]. We demonstrated in medication-free, righthanded female patients with BPD (N = 8), who were undergoing a 10-session psychiatric treatment, that hypotheses 1 and 2 may be confirmed (due to the small sample size, the analyses for hypotheses 3 and 4 were not tested).…”
Section: Feasibility: Results From the Pilot Studymentioning
confidence: 93%
“…We demonstrated feasibility of the pre-post design (50). We demonstrated for N = 8 medication-free right-handed female patients with BPD undergoing a 10-session psychiatric treatment that hypotheses 1 and 2 may be confirmed (due to the small sample size, the analyses for hypotheses 3 and 4 were not tested).…”
Section: Feasibility: Results From the Pilot Studymentioning
confidence: 93%
“…Both clients were diagnosed with BPD and received a brief 10‐session treatment as part of the study. More details on the study design, the treatment and the sample of this pilot study can be found in the original study that took place in a French‐speaking university environment (Kramer et al, ). We chose Linda and Suzan (names were changed in order to protect their identity) because of their marked between‐person differences in relationship patterns as reflected in their individualised stimuli (see Table ).…”
Section: Illustration Of a Study Applying This Methodology In The Conmentioning
confidence: 99%